Inhibition of Janus kinase/signal transducer and activator of transcription (JAK/STAT) signalling pathway in rheumatoid synovial fibroblasts using small molecule compounds. (24th October 2013) - Migita, K.; Izumi, Y.; Torigoshi, T.; Satomura, K.; Izumi, M.; Nishino, Y.; Jiuchi, Y.; Nakamura, M.; Kozuru, H.; Nonaka, F.; Eguchi, K.; Kawakami, A.; et al.
Summary: Janus kinase (JAK) inhibitors have been developed as anti‐inflammatory agents and have demonstrated clinical efficacy in rheumatoid arthritis (RA). We investigated if JAK‐3‐selective inhibition alone could disrupt cytokine signalling in rheumatoid synovial fibroblasts. In‐vitro studies were performed using synovial fibroblasts isolated from patients with RA. Levels of activated JAK and signal transducer and activator of transcription (STAT) proteins were detected by immunoblot analysis. Target‐gene expression levels were measured by reverse transcription–polymerase chain reaction (RT–PCR) or real‐time PCR. The JAK inhibitors CP‐690, 550 and INCB028050 both suppressed activation of JAK‐1/‐2/‐3 and downstream STAT‐1/‐3/‐5, as well as the expression levels of target proinflammatory genes ( MCP‐I, SAA1/2 ) in oncostatin‐M (OSM)‐stimulated rheumatoid synovial fibroblasts. In contrast, the JAK‐3‐selective inhibitor, PF‐956980, suppressed STAT‐1/‐5 activation but did not affect STAT‐3 activation in OSM‐stimulated rheumatoid synovial fibroblasts. In addition, PF‐956980 significantly suppressed MCP‐1 gene expression, but did not block SAA1/2 gene expression in OSM‐stimulated rheumatoid synovial fibroblasts. These data suggest that JAK‐3‐selective inhibition alone is insufficient to control STAT‐3‐dependent signalling in rheumatoid synovial fibroblasts, and inhibition of JAKs, including JAK‐1/‐2, is needed to control the proinflammatory cascade in RA.